Pengaruh Budaya Organisasional dan Kepribadian Terhadap Organizational Citizenship Behavior dengan Komitmen Organisasional Sebagai Mediasi : Studi pada Satuan Lalu Lintas Kepolisian Resor Kota Pati - Syafrudin Candra Prayikno; Euis Soliha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyze and describe the influence of organizational culture and personality on Organizational Citizenship Behavior mediated by organizational commitment on Traffic Unit of Pati City Police Resort. The population used in this study were 102 members of Traffic Unit of Pati City Police Resort. The sampling method in this study used census. Data analysis technique used regression using SPSS program and Sobel test. The results of this study can be concluded that organizational culture has a positive effect on organizational commitment. Personality has a positive effect on organizational commitment. Organizational culture has a positive effect on OCB. Personality has a positive effect on OCB. Work motivation has a positive effect on employee performance. Organizational commitment is able to mediate the influence of organizational culture on OCB. Organizational commitment is able to mediate the influence of personality on OCB.